Contribution of Ukrainian Scientists to the Development of Technology - Buyak, B.B.; Korsun, I.V.; Matsyuk, V.M. (Science and Innovation, 2024)
Introduction. Today, we can use phrase “the world’s first” for many inventions of Ukrainian scientists. Ukraine is a country with a high level of science development. As a proof of this statement, one may take the international recognition of achievements made by Ukrainian scientists in different areas of technology. Problem Statement. Ukraine aspires to become an equal member of the European Union. It is important that Ukrainians do not lose their national identity in this direction of movement. Disseminating knowledge about Ukrainian scientists is one of the ways to increase Ukraine's recognition in the world. That is why it is necessary to demonstrate to the world community the achievements of Ukrainian scientists and their high scientific level. Purpose. The research is aimed at justifying importance of Ukrainian scientists’ works for the development of technology in the world. Materials and Methods. The analytical review of the works of Ukrainian scientists that have the great importance for the development of technology in the world, was carried out. Results. The importance of Ukrainian scientists’ works in photography, cinematograph, electric welding, computer technology, aviation, astronomy, rocket science and astronautics has been proved. Ukrainian scientists were among the first in the invention of television, electric tram and radio control. Thanks to the work of our compatriots, it became possible to launch the first artificial satellite of the Earth, to make the flight of man to space, the exit of man in open space and landing on the surface of the Moon. Conclusions. Priority of Ukrainian scientists' works in many researches testifies to their significant contribution to the development of world technologies. Coverage of this contribution should by no means ignite interethnic animosity, but it can serve as an incentive to realize the national identity of Ukrainians in the context of world integration. The main principle is that science should unite peoples, and be the foundation of peace in the world. Given that Ukraine has significant achievements in science and technology, further research in this area is appropriate.